The neuromuscular features of acromegaly: a clinical and pathological study. Issue 9 (September 1984) - Khaleeli, A A; Levy, R D; Edwards, R H; McPhail, G; Mills, K R; Round, J M; Betteridge, D J
Abstract : A study of the neuromuscular features of acromegaly was performed in six patients. Clinical assessment was supplemented by quadriceps force measurements, plasma creatine kinase (CK) activities, electromyography (EMG) and nerve conduction studies. Muscle mass was measured by urinary creatinine/height indices (CHI) and cross sectional area (CSA) of thighs and calves on computed tomography. Quadriceps force/unit cross sectional area was derived. Needle biopsies of vastus lateralis were studied by histochemical and ultrastructural methods. Mean fibre area (MFA) and fibre type proportions were measured. Most of the subjects studied had muscle pain and proximal muscle weakness confirmed by quadriceps force measurements. This occurred in the absence of muscle wasting, as shown by cross sectional area measurements and normal or raised creatinine/height indices. "Myopathic" features were demonstrated by needle biopsy in half the patients and occasionally by electromyography and raised plasma creatine kinase activity. Abnormalities on needle biopsy included variation in fibre size, type 2 fibre atrophy and large type 1 MFA relative to type 2 MFA. Electronmicroscopy showed the non-specific findings of increased glycogen accumulation, excess lipofuscin pigment and myofilament loss.